Almost complex surfaces in the nearly Kaehler S6 - Sharief Deshmukh (International Journal of Mathematics and Mathematical Sciences)
It is shown that a compact almost complex surface in S6 is either totally geodesic or the minimum of its Gaussian curvature is less than or equal to 1/3.